Diabetes Mellitus Inhibits Hair Follicle Regeneration by Inducing Macrophage Reprogramming-Mediated Pyroptosis - Wang M; Lai Z; Zhang H; Yang W; Zheng F; He D; Liu X; Zhong R; Qahar M; Yang G (Dove Medical Press, 2024)
Minghui Wang,1,* Zhiwei Lai,1,* Hua Zhang,1,* Weiqi Yang,2 Fengping Zheng,1 Dehua He,2 Xiaofang Liu,2 Rong Zhong,2 Mulan Qahar,1,2 Guang Yang1- 3 1Division of Renal Medicine, Peking University Shenzhen Hospital, Peking University, Shenzhen, 518036, People's Republic of China; 2Department of Burn and Plastic Surgery, Shenzhen Institute of Translational Medicine, Shenzhen Second People's Hospital, The First Affiliated Hospital of Shenzhen University, Shenzhen, 518035, People's Republic of China; 3Department of Life Sciences, Yuncheng University, Yuncheng, 044011, People's Republic of China*These authors contributed equally to this workCorrespondence: Guang Yang; Mulan Qahar, Email yakoaka@foxmail.com; mulanqahar@126.comBackground: Diabetes mellitus (DM) is known to inhibit skin self-renewal and hair follicle stem cell (HFSC) activation, which may be key in the formation of chronic diabetic wounds. This study aimed to investigate the reasons behind the suppression of HFSC activation in DM mice.Methods: Type 1 DM (T1DM) was induced in 6-week-old mice via streptozotocin, and hair follicle growth was subsequently monitored. RNA sequencing, bioinformatics analyses, qRT‒PCR, immunostaining, and cellular experiments were carried out to investigate the underlying mechanisms involved.Results: T1DM inhibited HFSC activation, which correlated with an increase in caspase-dependent programmed cell death. Additionally, T1DM triggered apoptosis and pyroptosis, predominantly in HFSCs and epidermal regions, with pyroptosis being more pronounced in the inner root sheath of hair follicles. Notably, significant cutaneous immune imbalances were observed, particularly in macrophages. Cellular experiments demonstrated that M1 macrophages inhibited HaCaT cell proliferation and induced cell death, whereas high-glucose environments alone did not have the same effect.Conclusion: T1DM inhibits HFSC activation via macrophage reprogramming-mediated caspase-dependent pyroptosis, and there is a significant regional characterization of cell death. Moreover, T1DM-induced programmed cell death in the skin may be more closely related to immune homeostasis imbalance than to hyperglycemia itself. These findings shed light on the pathogenesis of diabetic ulcers and provide a theoretical basis for the use of hair follicle grafts in wound repair.Keywords: diabetes mellitus, caspases, hair follicle stem cells, chronic wounds, cutaneous immune disorder